Analisis Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Economic Order Quantity (Studi Kasus Pada Koperasi Wanita Patra Kasim Sorong-Papua Barat) - Rais Dera Pua Rawi; Wisang Candra Bintari; Ramli Lewenussa; Bekti Wiji Lestari; Retno Dewi Wijiastuti; I Gusti Ayu Arista Nada Dewi (Jurnal Akuntansi dan Pajak, 2022)
Raw material inventory is one of the important factors in carrying out a production. Shortage of raw materials will result in obstruction of the production process, while excess raw materials will result in swelling of storage costs and other costs. Through optimal inventory control, the company can determine the right order quantity and minimize inventory costs so that company goals can be achieved. The purpose of this study was to determine and analyze the control of raw material supplies applied in the Patra Kasim Sorong Women's Cooperative in West Papua. This type of research uses a quantitative approach with descriptive methods by explaining how the company applies raw material inventory control and then the data obtained is analyzed using the Economic Order Quantity (EOQ) method. The data used are primary data in the form of interviews. The results showed that the control of raw material supplies implemented by the Patra Kasin Sorong-West Papua Women's Cooperative was not optimal. The company is able to meet consumer demand, but the company has not been able to minimize inventory costs. When calculated using the EOQ method, the company can save on inventory costs with fewer quantities and frequency of purchases of main raw materials but takes into account safety stock and reorder points.